2015
DOI: 10.3390/cryst6010006
|View full text |Cite
|
Sign up to set email alerts
|

Constructor Graphs as Useful Tools for the Classification of Hydrogen Bonded Solids: The Case Study of the Cationic (Dimethylphosphoryl)methanaminium (dpmaH+) Tecton

Abstract: Abstract:The structural chemistry of a series of dpmaH (dpmaH = (dimethylphosphoryl)methanaminium) salts has been investigated using constructor graph representations to visualize structural dependencies, covering the majority of known dpmaH salts. It is shown that the structurally related α-aminomethylphosphinic acid can be integrated in the systematology of the dpmaH salts. Those dpmaH salts with counter anions that are weak hydrogen bond acceptors (ClO 4´, SnCl 6 2´, IrCl 6 2´, I´) tend to form head-to-tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…In the course of this study, the new compound caffHI 3 • caff was obtained. The appearance of this compound was expected, as we have already shown that depending on the pH value organic aminium halogenides cocrystals containing the organic aminium cation, the counter anion and one additional equivalent of the neutral organic amine can be easily obtained [11,14,15]. Even though caffeine has been known for many decades, studies on the medical and biological properties are still in progress [16].…”
Section: Commentmentioning
confidence: 88%
“…In the course of this study, the new compound caffHI 3 • caff was obtained. The appearance of this compound was expected, as we have already shown that depending on the pH value organic aminium halogenides cocrystals containing the organic aminium cation, the counter anion and one additional equivalent of the neutral organic amine can be easily obtained [11,14,15]. Even though caffeine has been known for many decades, studies on the medical and biological properties are still in progress [16].…”
Section: Commentmentioning
confidence: 88%